Exploring the potential of exfoliated ternary ultrathin Ti4AlN3 nanosheets for fabricating hybrid patterned polymer brushes1. Issue 86 (18th September 2015) - Ye, Qun; Xiao, Peng; Liu, Wulong; Chen, Ke; Chen, Tao; Xue, Jianming; Du, Shiyu; Huang, Qing
<x xml:space="preserve">Abstract</x> A new type of ternary Ti4AlN3 nanosheets was prepared for the first time. The obtained sheets with surface groups could be further used to fabricate micro-patterns and subsequently functionalized to achieve hybrid patterned polymer brushes.